Influence of Fish Oil-Derived n-3 Fatty Acid Supplementation on Changes in Body Composition and Muscle Strength During Short-Term Weight Loss in Resistance-Trained Men - Philpott, Jordan D.; Bootsma, Niels J.; Rodriguez-Sanchez, Nidia; Hamilton, David Lee; MacKinlay, Elizabeth; Dick, James; Mettler, Samuel; Galloway, Stuart D. R.; Tipton, Kevin D.; Witard, Oliver C. (Frontiers in Nutrition, 2019)
Background: A detrimental consequence of diet-induced weight loss, common in athletes who participate in weight cutting sports, is muscle loss. Dietary omega-3 polyunsaturated fatty acids (n-3PUFA) exhibit a protective effect on the loss of muscle tissue during catabolic situations such as injury-simulated leg immobilization. This study aimed to investigate the influence of dietary n-3PUFA supplementation on changes in body composition and muscle strength following short-term diet-induced weight loss in resistance-trained men. Methods: Twenty resistance-trained young (23 ± 1 years) men were randomly assigned to a fish oil group that supplemented their diet with 4 g n-3PUFA, 18 g carbohydrate, and 5 g protein (FO) or placebo group containing an equivalent carbohydrate and protein content (CON) over a 6 week period. During weeks 1–3, participants continued their habitual diet. During week 4, participants received all food items to control energy balance and a macronutrient composition of 50% carbohydrate, 35% fat, and 15% protein. During weeks 5 and 6, participants were fed an energy-restricted diet equivalent to 60% habitual energy intake. Body composition and strength were measured during weeks 1, 4, and 6. Results: The decline in total body mass (FO = −3.0 ± 0.3 kg, CON = −2.6 ± 0.3 kg), fat free mass (FO = −1.4 ± 0.3 kg, CON = −1.2 ± 0.3 kg) and fat mass (FO = −1.4 ± 0.2 kg, CON = −1.3 ± 0.3 kg) following energy restriction was similar between groups (all p > 0.05; d: 0.16–0.39). Non-dominant leg extension 1 RM increased (6.1 ± 3.4%) following energy restriction in FO (p < 0.05, d = 0.29), with no changes observed in CON (p > 0.05, d = 0.05). Dominant leg extension 1 RM tended to increase following energy restriction in FO (p = 0.09, d = 0.29), with no changes in CON (p > 0.05, d = 0.06). Changes in leg press 1 RM, maximum voluntary contraction and muscular endurance following energy restriction were similar between groups (p > 0.05, d = 0.05). Conclusion: Any possible improvements in muscle strength during short-term weight loss with n-3PUFA supplementation are not related to the modulation of FFM in resistance-trained men.